Screening of potential biosurfactant-producing yeasts isolated from the mangroves of the Paranaguá Estuarine Complex (PEC) (Acta Scientiarum. Biological Sciences, 2025)
Mangroves have been critical to discovering microbial diversity and for their use in biotechnological resources. The Paranaguá Estuarine Complex (PEC) is surrounded by mangroves that are exposed to anthropogenic actions resulting from industrial and seaport activities. The present study evaluated the molecular diversity of mangrove yeast isolates obtained from the PEC. Furthermore, the ability of these microorganisms to degrade oil was researched using the redox indicator 2,6-dichlorophenol indophenol (DCPIP) and dehydrogenase activity assays. Biosurfactant production was screened using the blue agar plate method, drop-collapse test, tilted glass slide test, oil spreading method, and emulsification assay. Internal Transcribed Spacer (ITS) sequencing revealed a great diversity of yeast species in the PEC, including Candida sp., C. parapsilosis, C. tropicalis, Meyerozyma carpophila, M. guilliermondii, and Debaryomyces hansenii. The isolates D. hansenii A2M1(1A), M. carpophila P2M5(74), and Candida sp. P2M3(74) tested positive for DCPIP and dehydrogenase activity. All isolates showed positive results in the blue agar plate method. The isolates M. carpophila A2M3(20), D. hansenii A2M3(15), C. tropicalis A2C5(2), C. parapsilosis A2C5, and M. carpophila P2M3(42) indicated activity in the tilted glass slide test. The isolates C. tropicalis A2C5(2), M. carpophila P2M3(42), and M. carpophila P2M5(74) showed activity in the emulsification assay. These findings provide important information about the composition of yeasts in the PEC mangrove, highlighting their potential for application in bioremediation processes of environments contaminated by petroleum.